Surface environmental monitoring system - Rudzenis, A. (ХНУРЕ, 2025)
Climate change monitoring is one of the most critical tasks of our time, as climate change has a profound impact on the environment, the economy, and human safety. Traditional monitoring methods have several limitations, high lighting the need for new solutions. Developing a monitoring system based on LoRaWAN, GPS, and satellite communication offers new opportunities to improve forecasting accuracy and expand geographic coverage, including remote and hard-to-reach areas.
Keywords: monitoring system; Climate change monitoring